The Importance of Direct Routes for Air Travel Itinerary Choices: Results from a Stated Preference Choice Experiment - Moleman, Milan; Kroesen, Maarten; Zijlstra, Toon; Faber, Roel (European Journal of Transport and Infrastructure Research, 2024)
Over the past years, aviation policies are more and more focussed on sustainability rather than connectivity, putting pressure on airlines to re-design the network. For this, evaluating air travellers their preferences on direct routing compared to lay-overs is needed to make well-informed design choices. This paper examines the preferences of air travellers on direct itineraries by applying a data-driven approach. To this end, a stated preference choice experiment is developed and implemented in an online survey. The results of the latent class choice model show two types of flyers with different preferences, labelled as time sensitive and price sensitive flyers. The model outcomes indicate that both are willing to pay for direct itineraries, while time sensitive flyers are willing to pay substantially more. Other flight characteristics also play an important role in air travellers’ route choice, such as the distance to the airport, travel time, and transfer time. Travel motive, ticket price compensation by the employer, and experience with layovers drive whether air travellers belong to the time or price sensitive flyers. The distinction between time and price sensitive flyers and their preferences is expected to yield more tailored transport policies than a distinction between, for instance, business and non-business. Future research should focus on the societal impact of a reduction in direct itineraries for air travellers, using insights gained in this study.